Mathematical Method for Predicting Nickel Deposit Based on Data from Drilling Points - Edi Cahyono; Sapto Rahardjo; Asrul Sani (Jurnal Teknik Industri: Jurnal Keilmuan dan Aplikasi Teknik Industri, 2011)
In this article we discuss several methods for predicting nickel ore content inside the soil under a given area/region. The prediction is the main objective of the exploration activity which is very important for conducting the exploitation activity from economic point of view. The prediction methods are based on the data obtained from the drilling activity at several ‘points’. The data yields information on the nickel density at those points. Nickel density over the region is approximated (with an approximate function) by applying interpolation and/or extrapolation based on the data from those points. The nickel content is predicted by applying integral of the approximate function over the given region